2021
DOI: 10.1007/s40544-021-0494-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of two polyphenols on the structure and lubrication of salivary pellicle: An in vitro study on astringency mechanism

Abstract: This study investigated the influence of two polyphenols on the structure and lubrication of the salivary pellicle, aiming to extend the understanding of astringency mechanisms. The salivary pellicle was prepared by the adsorption of human whole saliva on the enamel substrate. Low-astringency catechin and high-astringency tannic acid were used as astringents. The changes induced by the two polyphenols in the structure and lubrication of the salivary pellicle were examined using quartz crystal microbalance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Typically associated with red wine, green tea, and chocolate (Bajec & Pickering, 2008 ; Jöbstl et al, 2004; Peynaud & Blouin, 1996 ), astringency results from the exposure of oral surfaces to specific substances, especially polyphenol compounds (Lesschaeve & Noble, 2005 ). Importantly, astringent substances are thought to reduce lubricity, resulting in a subsequent increase in friction between those oral surfaces that stimulate mechanoreceptors thus giving rise to the “roughing” sensations that are experienced (Bajec & Pickering, 2008 ; De Wijk & Prinz, 2005 ; Gibbins & Carpenter, 2013 ; Lei et al, 2022 ), and paving the way for the idea that astringency may be a tactile stimulus that is perceived in a manner closely resembling the perception of tactile roughness (Breslin et al, 1993 ; Green, 1993 ; Kallithraka et al, 1998 ). Notably, Breslin et al ( 1993 ) demonstrated that the sensation of astringency can be elicited in the oral cavity in regions where there are no taste receptors, such as the upper lips, lending support to the tactile nature of astringency perception.…”
Section: Food Texture Astringency and (Oral-somatosensory) Roughnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically associated with red wine, green tea, and chocolate (Bajec & Pickering, 2008 ; Jöbstl et al, 2004; Peynaud & Blouin, 1996 ), astringency results from the exposure of oral surfaces to specific substances, especially polyphenol compounds (Lesschaeve & Noble, 2005 ). Importantly, astringent substances are thought to reduce lubricity, resulting in a subsequent increase in friction between those oral surfaces that stimulate mechanoreceptors thus giving rise to the “roughing” sensations that are experienced (Bajec & Pickering, 2008 ; De Wijk & Prinz, 2005 ; Gibbins & Carpenter, 2013 ; Lei et al, 2022 ), and paving the way for the idea that astringency may be a tactile stimulus that is perceived in a manner closely resembling the perception of tactile roughness (Breslin et al, 1993 ; Green, 1993 ; Kallithraka et al, 1998 ). Notably, Breslin et al ( 1993 ) demonstrated that the sensation of astringency can be elicited in the oral cavity in regions where there are no taste receptors, such as the upper lips, lending support to the tactile nature of astringency perception.…”
Section: Food Texture Astringency and (Oral-somatosensory) Roughnessmentioning
confidence: 99%
“…In addition to behavioural studies, research has investigated the physiological and physical mechanisms affecting the perception of astringency, including saliva composition, flow rate, and the disruption/alteration of the salivary pellicle (Gibbins & Carpenter, 2013 ; Upadhay et al, 2016 ). Recently, Lei et al ( 2022 ) demonstrated that when encountering tannic acid solution, the roughness of the salivary pellicle increases significantly, and lubrication performance is impaired due to the significant effect of tannic acid molecules on the structure of the salivary pellicle itself. Hence, astringency is generated by the increase of intraoral friction due to the structural changes in salivary pellicle caused by polyphenolic molecules introduced into the oral cavity.…”
Section: Food Texture Astringency and (Oral-somatosensory) Roughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…An artificial tongue substrate was developed, based on the topographic characteristics of human tongue and the morphological features of fungiform and filiform papillae and applied to investigate under different speeds and lubricants [731]. Two polyphenols were adopted to investigate the structure and lubrication of salivary pellicle, with a particular reference to astringency mechanism [732]. The effects of oral lubrication on satiety, satiation, and salivary biomarkers were investigated, as a potential novel strategy to reduce obesity [733].…”
Section: Oralmentioning
confidence: 99%
“…These results indicate that the selective adsorption of components over the functional layer is a complex phenomenon that does not depend only on the exposed functional groups. QCM-D was also used for the analysis of potential wine contaminations [ 31 ], and to study the interactions between wine compounds and salivary proteins [ 32 , 33 , 34 ], with the fascinating aim to compare measured data with the human mouthfeel [ 35 ]. To the best of our knowledge, QCM-D has not yet been used for wine polyphenol detection.…”
Section: Introductionmentioning
confidence: 99%